2009
DOI: 10.1021/es9006383
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induced by Zero-Valent Iron Nanoparticles and Fe(II) in Human Bronchial Epithelial Cells

Abstract: To identify the mechanism through which nanoparticulate zero-valent iron (nZVI; Fe0(s)) damages cells, a series of experiments were conducted in which nZVI in phosphate-buffered saline (PBS) was exposed to oxygen in the presence and absence of human bronchial epithelial cells. When nZVI is added to PBS, a burst of oxidants is produced as Fe0 and ferrous iron (Fe[II]) are converted to ferric iron (Fe[II]). Cytotoxicity and internal reactive oxygen species (ROS) production in cells exposed to nZVI is equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
124
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(137 citation statements)
references
References 44 publications
8
124
0
5
Order By: Relevance
“…However, despite the low cost and high efficiency of Fe 0 NPs in removing contaminants, [1][2][3][4][5][6] there are concerns that Fe 0 NP application contributes to long-term impacts on environmental and human health risks. [7][8][9][10][11][12][13][14][15][16][17] Moreover, the increasing use of Fe 0 NPs in in situ groundwater remediation could lead to large numbers of NPs released into the environment and is highly likely to pose potential exposure risks. 8 Several studies have indicated that Fe 0 NPs could cause cytotoxicity in human bronchial epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, despite the low cost and high efficiency of Fe 0 NPs in removing contaminants, [1][2][3][4][5][6] there are concerns that Fe 0 NP application contributes to long-term impacts on environmental and human health risks. [7][8][9][10][11][12][13][14][15][16][17] Moreover, the increasing use of Fe 0 NPs in in situ groundwater remediation could lead to large numbers of NPs released into the environment and is highly likely to pose potential exposure risks. 8 Several studies have indicated that Fe 0 NPs could cause cytotoxicity in human bronchial epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] Moreover, the increasing use of Fe 0 NPs in in situ groundwater remediation could lead to large numbers of NPs released into the environment and is highly likely to pose potential exposure risks. 8 Several studies have indicated that Fe 0 NPs could cause cytotoxicity in human bronchial epithelial cells. 8,18,19 Previous studies on the effects of Fe 0 NPs on microorganisms, such as Bacillus cereus, Pseudomonas stutzeri, and Escherichia coli, have revealed that Fe might be reduced from NPs to lead to stress responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One latest study showed that, after 12 weeks of inhalation tests, small TiO 2 nanoparticles 20 nm in size were characterized by a longer retention time in the lungs of rats and increased translocation to interstitial sites than larger TiO 2 nanoparticles 250 nm in size [4,[50][51][52]. Another study in healthy animals also showed that inhalation of metallic nanoparticles (less than 30 nm) into the circulatory system was much faster than that of non-metallic nanoparticles (between 4 nm and 200 nm) [53].…”
Section: Toxicity Of Nanomaterials and Lung Diseasementioning
confidence: 99%
“…Longterm toxicity of nanomaterials and examination of chronic exposure must be studied in detail to understand the mechanisms involved. Even though several factors are involved in nanomaterial toxicity, more efforts and time are needed to conduct research on nanoscale products and lung and other diseases [6,50].…”
Section: Toxicity Of Nanomaterials and Lung Diseasementioning
confidence: 99%